Quantitative Analysis of Phytosterols in Edible Oils Using APCI Liquid Chromatography–Tandem Mass Spectrometry. Issue 9 (25th July 2013) - Mo, Shunyan; Dong, Linlin; Hurst, W. Jeffrey; van Breemen, Richard B.
Abstract: Previous methods for the quantitative analysis of phytosterols have usually used GC–MS and require elaborate sample preparation including chemical derivatization. Other common methods such as HPLC with absorbance detection do not provide information regarding the identity of the analytes. To address the need for an assay that utilizes mass selectivity while avoiding derivatization, a quantitative method based on LC–tandem mass spectrometry (LC–MS–MS) was developed and validated for the measurement of six abundant dietary phytosterols and structurally related triterpene alcohols including brassicasterol, campesterol, cycloartenol, β‐sitosterol, stigmasterol, and lupeol in edible oils. Samples were saponified, extracted with hexane and then analyzed using reversed phase HPLC with positive ion atmospheric pressure chemical ionization tandem mass spectrometry and selected reaction monitoring. The utility of the LC–MS–MS method was demonstrated by analyzing 14 edible oils. All six compounds were present in at least some of the edible oils. The most abundant phytosterol in all samples was β‐sitosterol, which was highest in corn oil at 4.35 ± 0.03 mg/g, followed by campesterol in canola oil at 1.84 ± 0.01 mg/g. The new LC–MS–MS method for the quantitative analysis of phytosterols provides a combination of speed, selectivity and sensitivity that exceed those of previous assays.